Implementation of rapid antimicrobial susceptibility testing combined with routine infectious disease bedside consultation in clinical practice (RAST-ID): a prospective single-centre study. (8th September 2020) - Valentin, Thomas; Koenig, Elisabeth; Prattes, Juergen; Wunsch, Stefanie; Loizenbaur, Tobias; Krause, Robert; Zollner-Schwetz, Ines
Abstract: Objectives: Recently, EUCAST released guidelines for rapid antimicrobial susceptibility testing (RAST) directly from positive blood culture bottles. The aim of our prospective single-centre clinical study was to assess the proportion of readable results and errors compared with routine antimicrobial susceptibility testing and the clinical consequences drawn by infectious disease (ID) physicians from RAST results during same-day bedside consultation. Methods: All positive blood cultures suitable for RAST from January to December 2019 were included and RAST results at 4 and 6 h compared with standard disc diffusion. The real-life impact of RAST on clinical decisions was assessed during same-day ID bedside consultation. Results: The proportion of readable RAST results was significantly higher after 6 h of incubation compared with after 4 h (881/930 versus 642/847; P < 0.0001). Major and very major errors were rare (17/642 after 4 h and 12/881 after 6 h; P = 0.087). ID consultation was performed in 134 patients after the RAST result. Antimicrobial treatment was changed in 73 patients and 84 additional measures (i.e. imaging studies, surgery, additional resistance testing) were ordered in 62 patients. Conclusions: RAST according to EUCAST methods was easy to implement with a low number of major and very major errors after 6 h of incubation. ID physicians performing bedside consultations frequently used this information to change antimicrobial treatment and recommended additional measures.